Distinct profiles of cellular senescence-associated gene expression in the aged, diseased or injured central nervous system. (16th February 2022) - Pijewski, Robert S.; Sutter, Pearl A.; Duszak, Victoria A.; Singh, Neeraj; Yan, Riqiang; Smith, Phillip P.; Crocker, Stephen J.
Highlights: Aging, 5xFAD, and cuprizone models have unique transcriptional profiles of cellular senescence genes. PLAU is commonly upregulated in aging, 5xFAD, and cuprizone models. Cellular senescence gene expression profiles differ between 5xFAD mouse and human AD. Abstract: The molecular process of cellular senescence, which is known to contribute to aging, has been implicated in several diseases of the central nervous system (CNS). The purpose of this study was to generate an unbiased survey of cellular senescence gene expression with whole brain tissues using a standardized, curated set of 88 genes associated with cellular senescence. We performed a comparative analysis of aged brains with two CNS disease models; the 5xFAD mouse model of Alzheimer's disease, and cuprizone-induced CNS demyelination. Each experimental group could be distinguished from the others by expression of unique subsets of cellular senescence genes, with minimal overlap between each group. Gene ontology analyses identified unique processes within cellular senescence among each group. To examine how these changes translate to the human condition, we interrogated gene expression data from publicly available databases of human aging and AD cases which also corroborated our finding that cellular senescence gene expression changes in AD differ significantly from healthy aging, although the changes in human did not always correlate with the murine models. These data provide important insight on the common and unique global changes in expression of cellular senescence genes in the CNS accompanying aging, injury or disease. Future studies may define, using more refined cellular assays, the specific cellular phenotype differences, and how disparate drivers of unique disease pathologies all seemingly culminate in a common activation of cellular senescence.